Strategi Guru dalam Pemilihan dan Pemanfaatan Media Pembelajaran Sejarah di Sekolah Menengah - Fadillah, Alfiana Nurul; Sinambela, Rosi Daniela; Dalimunthe, Mutiara Nazla; Siahaan, Wahyu Renaldi; Purnamasari, Ika (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze teachers’ strategies in selecting, utilizing, and evaluating instructional media in history learning at the secondary school level, specifically at SMK Negeri 2 Medan. The research is based on the need to present historical concepts through visual and interactive media to enhance students’ understanding, especially among Generation Z learners who are highly familiar with digital technology. The study employed a field research method through in-depth interviews with a history teacher with nine years of teaching experience. The findings indicate that the teacher utilized various digital learning media such as instructional videos, digital museums, infographics, PowerPoint presentations, and interactive platforms to increase student engagement and motivation. The teacher also implemented differentiated instruction by grouping students based on their learning readiness, allowing the use of media to be adapted to students’ diverse needs. Digital media were found to be effective in clarifying abstract historical concepts and stimulating students' interest, although challenges remained, including limited facilities and varying levels of students’ digital literacy. To address these challenges, the teacher conducted continuous assessments, offered additional guidance, and developed more creative and contextual learning media. Overall, the study concludes that teachers' strategies in using digital media significantly contribute to creating history learning that is more engaging, meaningful, and relevant to current technological developments.